Analysis of the Relationship Between External Debt and Economic Growth and Development in Nigeria - Abalaka, J.N; Sulaiman T.H; Ajiteru,S.A.R (Green Economics: International Journal of Islamic and Economic Education, 2025)
With a focus on Nigeria specifically, this study examined the country's external debt and economic growth from 1985 to 2014. The underdevelopment of Nigeria is one of the study's main issues economy. Measuring how external debt affects the country's growth is one of the study's goals. According to the theoretical perspective, external debt is a tool of fiscal policy that closes the savings gap. The ex-post facto method of design was the research design employed in this study. With GDP as the dependent variable and multilateral debt, Paris Club debt, London Club debt, promissory notes, and other debt as the independent variables, the findings were analyzed using the ordinary least square multiple regression analytical approach. The hypotheses were tested using the Pearson correlation and the student T-test. All types of external indebtedness contributed to the GDP's development, according to the data analysis, the Pearson While the dependent variable had a direct link with the other independent variables, GDP had an inverse association with Paris Club debt and promissory notes, as described by correlation. In order to reject the null hypotheses and accept the alternative hypotheses, the tested hypotheses showed that each independent variable had a positive influence and was significant to the effect of the dependent variable. According to the study's findings, Nigeria's economic growth is significantly impacted by external debt, and as a result, better management of these borrowings is advised in order to achieve sustainable growth.